2013
DOI: 10.1091/mbc.e12-10-0728
|View full text |Cite
|
Sign up to set email alerts
|

Motion of variable-length MreB filaments at the bacterial cell membrane influences cell morphology

Abstract: Superresolution fluorescence microscopy shows that bacterial MreB forms filamentous structures of length up to 3.4 µm, which run at various angles underneath the cell membrane with a speed of 85 nm/s. Movement depends on ATPase activity. Thus MreB is a true orthologue of actin, whose extended filament architecture drives cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
84
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 50 publications
12
84
0
Order By: Relevance
“…It has been hypothesized that orientation inside the cell comes about due to binding of MreB polymers to the inner membrane and the energetics of polymer and membrane deformation (15). The length of MreB polymers has been the subject of considerable debate due to fluorescent-labeling artifacts, although the most recent published data and data presented in this study indicate that MreB forms short polymers about a micron in length (16,17).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…It has been hypothesized that orientation inside the cell comes about due to binding of MreB polymers to the inner membrane and the energetics of polymer and membrane deformation (15). The length of MreB polymers has been the subject of considerable debate due to fluorescent-labeling artifacts, although the most recent published data and data presented in this study indicate that MreB forms short polymers about a micron in length (16,17).…”
Section: Introductionmentioning
confidence: 72%
“…Above this level, A22 begins to bind nonspecifically to other proteins, which increases lethality (29). Future work on the MreB E143A mutant could shed light on MreB function as it is currently thought that the turnover of MreB monomers is physiologically necessary (17).…”
Section: Mreb Polymers In A22-treated Cells and The Effect Of A22 On mentioning
confidence: 99%
“…MreB forms filaments in the cytoplasm that are attached to the cytoplasmic membrane in both Gram-negative (Kruse et al 2003) and Gram-positive bacteria (Jones et al 2001;Olshausen et al 2013;Reimold et al 2013). The length of the MreB filaments is currently under debate, in particular because native-expression-level MreB filaments have not been detected in whole cells by electron microscopy (Swulius and Jensen 2012).…”
Section: Necessity For Regulationmentioning
confidence: 99%
“…The length of the MreB filaments is currently under debate, in particular because native-expression-level MreB filaments have not been detected in whole cells by electron microscopy (Swulius and Jensen 2012). Irrespective of their exact length, it has been shown by fluorescence microscopy that MreB filaments rotate around the long cell axis in a processive manner in Gram-negative (Teeffelen et al 2011) and Gram-positive bacteria (Garner et al 2011;Domín-guez-Escobar et al 2011;Olshausen et al 2013;Reimold et al 2013). This rotation depends on PG synthesis and proceeds at a speed compatible with processive insertion of single glycan strands into the PG meshwork (Teeffelen et al 2011), as already suggested by Burmann and Park in the 1980s (Burman and Park 1984).…”
Section: Necessity For Regulationmentioning
confidence: 99%
See 1 more Smart Citation